Setting time and mechanical properties of alkali-activated ash/slag cements cured at room temperature - Caetano, P.; Batista, T.; Nogueira, R.; Cabral, A.; Costa, H. (Revista Ingeniería de Construcción, 2023)
The focus of this paper is to investigate the behavior of the fresh and hardened state of alkali-activated cementitious pastes obtained from the mixture of bottom ash/BOF slag and fly ash/BOF slag. For this purpose, the properties in the fresh and hardened state were evaluated. Ten pastes were produced in two separate systems, whose proportions between ashes and BOF slag were 100:0, 75:25, 50:50, 25:75, and 0:100 (fly ash or bottom ash: BOF slag). In general, the addition of BOF steel slag works by accelerating the setting times, at room temperature curing. In addition, the stress-strain curves demonstrated that heavy ash and BOF steel slag favor the ductile behavior under axial stress. Furthermore, the addition of BOF slag can influence the properties in the fresh and hardened state. Therefore, it is feasible to use steel slag combined with coal ash in alkaline activated binary mixtures.